Financial Performance Of Indonesia Food And Beverage Subsector Companies : Good Corporate Governance And Gender Diversity - Muhamad Muslih; Namira Salsabila Ardiwinata (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this research is to investigate the effects of good corporate governance and gender diversity on financial performance. From 2018 to 2021, the population of this study is Food and Beverage Subsector firms registered on the Indonesia Stock Exchange. This study employed a purposive sample strategy to acquire 18 companies for four years in a row. The panel data regression analysis method was employed for the analysis. The findings of this study reveal that effective corporate governance and gender diversity both have an impact on the financial performance of food and beverage subsector companies listed on the IDX. Independent commissioners have an impact on financial performance, institutional ownership has an impact on financial performance, managerial ownership has an impact on financial performance and gender diversity has no impact on financial performance.